Applying the Prigogine view of dissipative systems to the major transitions in evolution. Issue 4 (November 2022) - de Castro, Carlos; McShea, Daniel W.
Abstract: Ilya Prigogine's trinomial concept is, he argued, applicable to many complex dissipative systems, from physics to biology and even to social systems. For Prigogine, this trinomial— functions, structure, fluctuations —was intended to capture the feedback-rich relations between upper and lower levels in these systems. The main novelty of his vision was his view of causation, in which the causal arrow runs downward from dissipative structures to their components or functions. Following this insight, some physicists and biophysicists are beginning to apply terms formerly used mainly in biology, such as evolution, adaptation, learning, and life-like behavior, to physical and chemical nonequilibrium systems. Here, instead, we apply Prigogine's view to biology, in particular to evolution, and especially the major transitions in evolution (MTE), arguing that at least the hierarchical transitions—the transitions in individuality—follow a trajectory anticipated by the trinomial. In this trajectory, formerly free-living organisms are transformed into "functions" within a larger organic "structure." The Prigogine view also predicts that, consistent with available data, the increase in number of hierarchical levels in organisms should accelerate over time. Finally, it predicts that, on geological timescales, ecosystems and Gaia in particular will tend to "de-Darwinize" or "machinify" their component organisms.